"Our lab is the community": Defining essential supporting infrastructure in engagement research. Issue 4 (27th November 2018) - Nease, Donald E.; Burton, Dee; Cutrona, Sarah L.; Edmundson, Lauren; Krist, Alex H.; Laws, Michael Barton; Tamez, Montelle
Abstract : Introduction: Effective patient engagement is central to patient-centered outcomes research. A well-designed infrastructure supports and facilitates patient engagement, enabling study development and implementation. We sought to understand infrastructure needs from recipients of Patient-Centered Outcomes Research Institute (PCORI) pilot grant awards. Methods: We surveyed recipients of PCORI pilot project awards on self-perceived strengths in engagement infrastructure through PCORI's Ways of Engaging-Engagement Activity Tool survey, and interviewed leaders of 8 projects who volunteered as exemplars. Descriptive statistics summarized the survey findings. We conducted a thematic analysis of the interview transcripts. Results: Of the 50 surveyed pilots, 22 answered the engagement infrastructure questions (44% response rate). Survey and interview findings emphasized the importance of committed institutional leadership, ongoing relationships with stakeholder organizations, and infrastructure funding through Clinical and Translational Science Awards, PCORI, and institutional discretionary funds. Conclusions: These findings highlight the importance of and how to improve upon existing institutional infrastructure.